2013
DOI: 10.1021/jf401628v
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity Assessment of Cerium Oxide Nanoparticles in Cilantro (Coriandrum sativum L.) Plants Grown in Organic Soil

Abstract: Studies have shown that CeO₂ nanoparticles (NPs) can be accumulated in plants without modification, which could pose a threat for human health. In this research, cilantro (Coriandrum sativum L.) plants were germinated and grown for 30 days in soil amended with 0 to 500 mg kg⁻¹ CeO₂ NPs and analyzed by spectroscopic techniques and biochemical assays. At 125 mg kg⁻¹, plants produced longer roots (p ≤ 0.05), and at 500 mg kg⁻¹, there was higher Ce accumulation in tissues (p ≤ 0.05). At 125 mg, catalase activity s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
70
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(83 citation statements)
references
References 49 publications
12
70
1
Order By: Relevance
“…Notably, this study was conducted in cell culture and more investigation in soil-based systems will be needed. In a final soil study, Morales et al 85 noted that nanoceria at concentrations up to 500 mg/kg had no impact on cilantro shoot biomass and in some instances, increased root growth. However, the authors did report FTIR-detected changes in carbohydrate chemistry, which raises the potential for altered nutritional content in edible tissues.…”
Section: Soil Exposures In Plantsmentioning
confidence: 99%
“…Notably, this study was conducted in cell culture and more investigation in soil-based systems will be needed. In a final soil study, Morales et al 85 noted that nanoceria at concentrations up to 500 mg/kg had no impact on cilantro shoot biomass and in some instances, increased root growth. However, the authors did report FTIR-detected changes in carbohydrate chemistry, which raises the potential for altered nutritional content in edible tissues.…”
Section: Soil Exposures In Plantsmentioning
confidence: 99%
“…In contrast, other studies have reported that NPs, such as TiO 2 , cerium oxide (CeO 2 ), zinc oxide (ZnO), g-Fe 2 O 3 , could also cause damage in plants, including decreases in photosynthesis efficiency (Lei et al, 2007;Ze et al, 2011), chlorophyll degradation, total protein reduction (Krystofova et al, 2013;Zhao et al, 2013), as well as micro and macro-nutrient displacement Zhao et al, 2014a). Oxidative stresses caused by NPs could activate defense mechanisms to counteract nanotoxicity in plants ( Morales et al, 2013;Rico et al, 2013;Servin et al, 2013). Many publications have reported the main reason of toxicity upon NPs exposure, but results were contradictory.…”
Section: Introductionmentioning
confidence: 98%
“…Also, SiO 2 nanoparticles can increase root length at 400 mg/L (Lee et al 2010) and CeO 2 nanoparticle suspensions promoted the root growth of corn and cucumber, even though the germination rate declined (Lopez-Moreno et al 2010). Cilantro grown in organic potting soil had longer shoots and larger roots with CeO 2 nanoparticles (Morales et al 2013). Arabidopsis grown in MS media containing Al 2 O 3 nanoparticles had longer roots (Lee et al 2010) and TiO 2 nanoparticles can also increase the chlorophyll content of Arabidopsis (Lenaghan et al 2013).…”
Section: Positive Effects Of Nanoparticlesmentioning
confidence: 96%
“…Toxicity assessment of CeO 2 nanoparticles in cilantro grown in organic soil showed that the activity of catalyze and ascorbate peroxidase increased significantly only at a concentration 125 mg/kg (Morales et al 2013). Four edible plants, including alfalfa, corn, cucumber, and tomato, show differential responses to CeO 2 nanoparticles (Lopez-Moreno et al 2010).…”
Section: Factors Affecting the Toxicity Of Nanoparticlesmentioning
confidence: 99%